VARIABEL-VARIABEL YANG MEMPENGARUHI SEMANGAT KERJA PEGAWAI NEGERI SIPIL PADA SATUAN POLISI PAMONG PRAJA PROVINSI KALIMANTAN TIMUR - . Mahlan (Magister Administrasi Publik FISIP Universitas Mulawarman, 2019)
Writing and research, including the type of causal research comparative quantitative approach performed on Civil Service Police Unit of East Kalimantan Province, aims to validate the hypothesis posed, or the relationship of influence between the variables of leadership, work environment, work culture, communication, supervision employment, compensation and placement on morale of civil servants at the municipal police Prov. Kaltim and to know which one is more dominant variable, using quantitative methods of correlation. Based on the results of research conducted by a few conclusions that there is a relationship of influence between the variables of leadership, work environment, work culture, communication, supervision of work, compensation, and placement on morale in a real and proven to significantly that, the variables that influence significantly to increase employee morale is monitoring the work.Keyword: leadership, work environment, work culture, communication, supervision of work, compensation, placement